Evaluating the Effects of Biodegradable and Conventional Modified Atmosphere Packaging on the Shelf Life of Organic Cavendish Bananas - Rahaman, Adams Abdul (Journal of Postharvest Technology, 2013)
The physiological disorders in banana fruits result in the reduction of fruit  quality and the market value that can manifest as diseases in consumer  packages. This study investigates the effects of the use of Biodegradable  (Bioflex) Modified Atmosphere Packaging (MAP) and LDPE Conventional  MAP on rate of ripening (colour changes) and overall consumer acceptance of  Cavendish banana fruits at 20°C and 80% RH for eight days. Banana fruits  stored in Biodegradable MAP showed quite lower weight loss as compared to  others. Fruits stored in Conventional MAP and without Package ripened  rapidly as compared with Biodegradable MAP. The CO2 concentration for the  Biodegradable MAP and Conventional MAP were 12% and 9.8% respectively.  The O2 Concentration decline gradually to 5.2% for Biodegradable MAP  compared with 2% for the Conventional MAP. Moreover, fruits stored in  Biodegradable MAP showed superior consumer acceptability.
Keywords: consumers; represented; physiological; acceptability.; Conventional